Demographics and Career Intentions of Graduates of Combined Baccalaureate–MD Programs, 2010–2017: An Analysis of AAMC Graduation Questionnaire Data. (January 2021) - Merritt, Rory; Baird, Janette; Clyne, Brian
Abstract : Purpose: Combined baccalaureate–MD programs exist to fulfill a variety of educational missions, including to promote the development of physician–scientists, increase workforce diversity, promote primary care careers, and meet the needs of underserved patients. The authors sought to determine the demographics of combined program graduates, as well as their intention to practice in primary care (IPPC) and intention to work with the medically underserved (IWMU), as compared with graduates of traditional MD programs. Method: Data from the 2010–2017 Association of American Medical Colleges Graduation Questionnaire, a national survey of graduating medical students, were recategorized (e.g., as combined program or traditional program) before analysis. Logistic regression models on the 2 primary outcomes (IPPC and IWMU) were conducted to estimate odds ratios for the effects of covariates and predictors (e.g., gender, underrepresented in medicine [URM] group member, type of medical degree program). Results: Data from a total of 109, 028 respondents were included (3, 182 from combined and 105, 846 from traditional programs). Compared with students in traditional programs, those in combined programs were more likely to be younger (age at graduation ⩽ 29: 3, 143, 98.8% vs 89, 688, 84.7%) and female (1, 813, 57.0% vs 52, 013, 49.1%) but less likely to identify as a URM group member (276, 8.7% vs 14, 757, 13.9%). In an adjusted logistic regression model, graduating from a combined program, identifying as female, and IWMU predicted significantly greater odds of IPPC, while identifying as a URM, identifying as female, and having debt predicted significantly greater odds of IWMU. Graduating medical students who indicated family medicine as a career specialty were more likely to indicate an IWMU. Conclusions: Medical students graduating from combined programs were more likely to indicate an IPPC but were no more likely to indicate an IWMU than traditional program graduates.